Theoretical Foundations of Research on the Pedagogical Teachings and Scientific Legacy of Great Astronomers - Saida, Avezmuradova (Journal of Innovation in Education and Social Research, 2025)
This article explores the theoretical foundations of studying the pedagogical teachings and scientific legacies of great astronomers throughout history. It discusses how astronomical discoveries influenced educational methods, scientific thought, and cultural development across civilizations. The study emphasizes the importance of integrating historical perspectives into modern pedagogical practices and highlights the didactic contributions of figures such as Ptolemy, Copernicus, Galileo, and Ulugh Beg. Through this analysis, the article seeks to demonstrate the enduring educational value of classical astronomical heritage in shaping scientific literacy and critical thinking.